The Role Of Media Literacy In The Image Of A Modern Teacher - Gulbahor Azamovna Ismoilova; Shakhnazakhon Ulugbek qizi Karimova (Euro Asian Journal Publishing, 2024)
This article discusses media literacy, which encompasses skills and competencies for receiving and evaluating mass media content, in the context of the rapid development of information and communication technologies
Keywords: internet; television; cinema; radio